The Issues Influencing of Environmental Accounting Information Systems: An Empirical Investigation of SMEs in Indonesia - Meiryani, Meiryani; Susanto, Azhar; Warganegara, Dezie Leonarda (International Journal of Energy Economics and Policy, 2018)
Recognizing the limitations in corporate environmental accounting systems, the present study examines the critical issues in the usefulness of Environmental Accounting Information Systems (EAIS). In this regard, the study investigates the impact of perceived environmental uncertainty (PEU), sophistication of information technology (ITS) and measuring errors in environmental cost (EEC) on EAIS alignment in Indonesian SMEs. The findings of Confirmatory Factor Analysis (CFA) lead to conclude that the conceptual model fulfills the goodness of fit criteria. Furthermore, the results of Structural Equation Modeling establish that sophistication of IT, measuring errors in environmental cost and perceived environmental uncertainty have significant impact in influencing the Alignment of Environment Accounting Information System in Indonesia. Keywords: Environmental Accounting Information Systems, Environmental Cost, IT sophistication, Environmental Uncertainty JEL Classifications: Q34, Q56, M00 DOI: https://doi.org/10.32479/ijeep.7231